Implementasi Nilai-Nilai Religius di SMP Muhammadiyah Tonjong Kabupaten Brebes - Risa Nasyiatul Ulfah; Makhful Makhful (Proceedings Series on Social Sciences & Humanities, 2023)
The phenomenon of juvenile delinquency, corruption, and events that deviate from religious values ??are now increasingly rampant. This phenomenon should not have happened in this well-known religious country. Therefore, education is one of the solutions in instilling religious values ??from an early age. The implementation of religious values ??is the foundation for future generations to lead this nation. The purpose of this study is to describe religious values ??and to know the role of teachers in implementing religious values ??in students at SMP Muhammadiyah Tonjong. This research is a type of field research, namely field research. The data sources used are primary data sources and secondary data sources. The methods for collecting data used in the study were interviews, observations and documentation. While the data analysis technique used is inductive through data reduction, data presentation and conclusions. The results of the study show that the implementation of religious values ??carried out by moral teachers at SMP Muhammadiyah Tonjong, applies to three values, namely: moral values ??on this value through giving advice and habituation. This advice is given by all teachers, especially moral teachers during KBM and the habituation carried out by teachers to students is 5S habituation (Smile, Greetings, Greetings, Polite, Courteous). The second value is the value of worship at this value through the refraction of congregational Dluha prayers and Friday prayers at school. As for what is done by the teacher in instilling the value of this worship, namely rotating cults before the KBM starts. The third value is the exemplary value, namely the teacher is an example or role model for students. In this example the teacher keeps his attitude and words. There are 6 roles of moral teachers in implementing these religious values, namely: teachers as role models, teachers as mentors, teachers as teachers, teachers as learning influences, teachers as facilitators and teachers paying attention or supervision to students.